2006
DOI: 10.1007/3-540-34422-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Self-Compression in the Nonlinear Propagation of Intense Femtosecond Laser Pulse in Normally Dispersive Solids

Abstract: Summary. The self-compression phenomena of intense femtosecond pulses in normally dispersive solids were investigated experimentally. Both un-chirped and negatively chirped laser pulses were used as input pulses. It is demonstrated that intense femtosecond laser pulses can be compressed by the nonlinear propagation in the transparent solids, and the temporal and spectral characteristics of output pulses were found to be significantly affected by the input laser intensity, with higher intensity corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…From Tzortzakis et al (2001d). filaments in BaF 2 and have interpreted the white light spectral distribution as resulting from plasma induced self-phase modulation. Chen et al (2006bChen et al ( , 2005 and Li et al (2006) have shown experimentally that high-power femtosecond pulses undergoing filamentation in a piece of BK7 glass lead to a self-compression from 50 to 20 fs, with a compression factor of about 2.5. However, the output pulse was observed to be split into two peaks when the input intensity is high enough to generate supercontinuum and conical emission as shown by Tzortzakis et al (2001d).…”
Section: Filamentation In Transparent Solidsmentioning
confidence: 97%
“…From Tzortzakis et al (2001d). filaments in BaF 2 and have interpreted the white light spectral distribution as resulting from plasma induced self-phase modulation. Chen et al (2006bChen et al ( , 2005 and Li et al (2006) have shown experimentally that high-power femtosecond pulses undergoing filamentation in a piece of BK7 glass lead to a self-compression from 50 to 20 fs, with a compression factor of about 2.5. However, the output pulse was observed to be split into two peaks when the input intensity is high enough to generate supercontinuum and conical emission as shown by Tzortzakis et al (2001d).…”
Section: Filamentation In Transparent Solidsmentioning
confidence: 97%